PRE-OPERATIVE EXPECTATIONS FOR RETURN TO SPORTS AND OUTCOMES FOLLOWING ACL RECONSTRUCTION: A SURVEY OF ADOLESCENT PATIENTS AND THEIR PARENTS. Issue 7 (30th July 2021) - Varakitsomboon, Shing; Saper, Michael
Background: There is limited data regarding patient and parent expectations regarding return to sport (RTS) and outcomes following anterior cruciate ligament reconstruction (ACLR) in adolescent athletes. Purpose: To investigate RTS and outcome expectations of adolescent patients and their parents before ACLR and determine any differences between groups. Methods: For this cross-sectional study, sets of patients (aged 10 to 18 years) and parents were separately asked to complete the same questionnaire relating to knowledge and expectations regarding the patient's upcoming ACLR. The custom survey consisted of 12 questions and was administered before being seen by a single sports medicine surgeon in the clinical setting of a tertiary care referral center from June 2019 through June 2020. Statistical analysis was performed to compare differences between patient and parent/guardian responses. Results: 28 sets of patients (53.6% female) and parents (64.3% female) completed the survey with average ages of 14.5 ± 2.0 years and 45.6 ± 7.0 years, respectively. 75% of families were Caucasian and 85.2% had private insurance. The most common sports played were basketball (25%) and soccer (17.9%). Overall, nearly 68% of consults were for a second opinion. 50% of patients and 82.1% of parents researched or read of ACL injuries and/or surgery prior to the visit. Most patients (46.4%) and parents (51.9%) expected the surgeon to consider full, unrestricted RTS/activities at 9 months. Only 7.1% of patients and 3.7% of parents believed full RTS would occur >12 months. 50% of patients and 67.9% of parents expected RTS at the same level. Both patients (53.6%) and parents (64.3%) believed fear of re-injury was the most common reason for not returning to sport or returning at a decreased level. There were no statistically significant differences in RTS expectations between patients and parents ( p >0.05). Most patients (38.5%) believed the risk of graft rupture in adolescent athletes was 5%, whereas most parents (37%) believed the risk to be at 25%, but the difference was not statistically significant ( p >0.05). Both patients and parents believed the risk of graft rupture was highest within the first 6 months (77.8% vs. 50%, respectively). More parents felt the risk of graft rupture was highest within the first year (39.3% vs. 22.2%), but the difference was not statistically significant ( p >0.05). Conclusion: Adolescent patients and their parents had similar knowledge and expectations regarding RTS and outcomes following ACLR. Further study is needed to better understand factors affecting those expectations.